2012
DOI: 10.1530/rep-11-0286
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal status of male recipient mice influences germ cell development in immature buffalo testis tissue xenograft

Abstract: Growth and development of immature testis xenograft from various domestic mammals has been shown in mouse recipients; however, buffalo testis xenografts have not been reported to date. In this study, small fragments of testis tissue from 8-week-old buffalo calves were implanted subcutaneously onto the back of immunodeficient male mouse recipients, which were either castrated or left intact (non-castrated). The xenografts were retrieved and analyzed 12 and 24 weeks later. The grafted tissue survived and grew in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…Tissues that were cryopreserved in 10% DMSO showed significant increase in tubular and lumen diameter 24 weeks after xenografting compared with the tubular and lumen diameter of donor tissue. This is suggestive of germ cell development and change in Sertoli cell morphology in frozen-thawed xenografts, as reported previously [23].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Tissues that were cryopreserved in 10% DMSO showed significant increase in tubular and lumen diameter 24 weeks after xenografting compared with the tubular and lumen diameter of donor tissue. This is suggestive of germ cell development and change in Sertoli cell morphology in frozen-thawed xenografts, as reported previously [23].…”
Section: Discussionsupporting
confidence: 88%
“…Immunolocalization of PCNA has been used for studying cell proliferation in developing testes [23]. In testis tissues that were grafted after cryopreservation in 10% DMSO, PCNA-stained germ cell number was similar to that in donor tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seminal vesicles from all autografted mice were weighed for assessment of the bioactive circulating testosterone level (Honaramooz et al 2002, Reddy et al 2012. Blood was collected from autografted mice at the time when being killed by cardiac puncture, and serum was subsequently collected by centrifugation.…”
Section: Autografted Mouse Analysismentioning
confidence: 99%
“…Successful generation of sperm from xenografts of immature testes from mice, hamsters, monkeys , bulls (Oatley et al 2005), pigs, goats (Honaramooz et al 2002), cats (Snedaker et al 2004), buffaloes (Reddy et al 2012) and mouse hosts has already been reported. Previous studies have shown that xenografted testis tissue from sexually mature donors is less successful than that from sexually immature donors (Arregui et al 2008).…”
Section: Introductionmentioning
confidence: 99%